2023
DOI: 10.1039/d2nr05000e
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial electron transfer in heterojunction nanofibers for highly efficient oxygen evolution reaction

Abstract: Efficient catalysts for oxygen evolution reactions (OER) are critical to the progress of electrochemical devices for clean energy conversion and storage. Although heterogeneous electrocatalysts have superior activity, it is a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…To date, catalysts derived from the noble metal iridium (Ir), along with their corresponding metal oxides, have demonstrated the capability to fulfill the necessary criteria for the practical implementation of PEMWE. The scarcity and relatively low intrinsic activity impede Ir-based catalysts for industrial-scale hydrogen (H 2 ) production. In contrast, ruthenium-based catalysts (particularly RuO 2 ) offer lower costs and higher activity, making them more promising for catalyzing the OER. However, the excessive oxidation of ruthenium leads to the production of highly soluble Ru species (Ru n + , n > 4), which accelerates catalyst degradation and significantly reduces electrochemical efficiency. The insufficient durability of these catalysts remains a critical obstacle in their utilization. , Thus far, numerous strategies, such as metal doping, engineered nanostructures, and fabricating heterostructures, have been proposed to enhance the activity and stability of RuO 2 . Notably, their electrochemical properties are also greatly influenced by the contact between the electrocatalysts and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…To date, catalysts derived from the noble metal iridium (Ir), along with their corresponding metal oxides, have demonstrated the capability to fulfill the necessary criteria for the practical implementation of PEMWE. The scarcity and relatively low intrinsic activity impede Ir-based catalysts for industrial-scale hydrogen (H 2 ) production. In contrast, ruthenium-based catalysts (particularly RuO 2 ) offer lower costs and higher activity, making them more promising for catalyzing the OER. However, the excessive oxidation of ruthenium leads to the production of highly soluble Ru species (Ru n + , n > 4), which accelerates catalyst degradation and significantly reduces electrochemical efficiency. The insufficient durability of these catalysts remains a critical obstacle in their utilization. , Thus far, numerous strategies, such as metal doping, engineered nanostructures, and fabricating heterostructures, have been proposed to enhance the activity and stability of RuO 2 . Notably, their electrochemical properties are also greatly influenced by the contact between the electrocatalysts and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…However, the scarcity and high cost of the noble metals pose serious obstacles to the widespread application of these technologies. [15][16][17] Researchers have been dedicated to designing and modifying non-precious electrocatalysts to achieve high catalytic activity and outstanding stability. Based on the physicochemical properties of the constituent elements in electrocatalysts, these elements can be roughly classified into three categories: (1) precious metal elements, with Pt being the most commonly used catalyst in advanced systems; [18][19][20][21] (2) non-precious metal elements, such as Ni, Co, Fe, Mo, Cu, and W, which can form alloys with each other or compounds with nonmetal elements; [22][23][24][25][26][27] (3) non-metal elements, mainly including B, N, C, P, S, and Se, which typically form compounds with metal elements.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, precious metals like Pt and metal oxides like RuO 2 and IrO 2 , are the most promising electrocatalysts for ORR, HER, and OER due to their excellent catalytic activity and long‐term stability under extreme working conditions. However, the scarcity and high cost of the noble metals pose serious obstacles to the widespread application of these technologies [15–17] . Researchers have been dedicated to designing and modifying non‐precious electrocatalysts to achieve high catalytic activity and outstanding stability.…”
Section: Introductionmentioning
confidence: 99%
“…Also using ab initio calculations, Varjovi et al 8 demonstrated the dynamical and thermal stability of Janus WXO (X = S, Se, and Te) monolayers, which were found to exhibit orientation dependent mechanical properties, a band gap that narrows along the chalcogen group, and large-piezoelectric properties. Experimentally, Fu et al 9 have shown how the fabrication of Sr 0.9 Ce 0.05 Fe 0.95 Ru 0.05 O 3 provided a potential heterostructure electrocatalyst when embedded into in situ grown RuO 2 . Captivating properties such as a second-harmonic generation (SHG) response, 10 strong Rashba spin splitting, 11 efficient catalytic performance 12 and a significant piezoelectric effect have been achieved due to quantum confinement effects that arise at the nanoscale, unlike in the bulk form.…”
Section: Introductionmentioning
confidence: 99%